A sofc stack containing a two-stage electrolyte
Patent Information
- Application Number
- CN202611055414.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-07-09
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本申请的目的是提供一种含有两段式电解质的SOFC电堆,通过采用两段电解质结构实现了温度梯度分区优化,同时兼顾高离子导电性和结构稳定性,解决了传统SOFC在高温操作下的热降解、密封失效和寿命短的问题
1、本申请的含有两段式电解质的SOFC电堆,高温电解质YSZ在高温区间具有优异的氧离子电导率和化学稳定性,可保证高温段的快速离子传输。中温电解质SDC在中温区间的电导率明显高于YSZ,弥补了YSZ在中温区的电导率不足。两段式设计使电解质在宽温域(500℃~800℃)内均保持高离子电导率,大幅降低欧姆极化损失,提升电池输出功率和能量转换效率。
Smart Images

Figure CN122930974A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of solid oxide fuel cell technology, specifically relating to an SOFC stack containing a two-stage electrolyte. Background Technology
[0002] Solid oxide fuel cells (SOFCs), as a highly efficient electrochemical energy conversion device, can directly convert the chemical energy of fuels (such as hydrogen and methane) into electrical energy. They have significant advantages such as high energy conversion efficiency (theoretical efficiency can reach 85%) and low pollutant emissions (the main products are water and carbon dioxide). They show broad application prospects in distributed power generation, portable power supplies and vehicle power systems, and are one of the important technological directions for addressing the energy crisis and environmental pollution problems.
[0003] Traditional SOFCs rely on the oxygen ion conductivity of their electrolyte materials for operation, with yttrium-stabilized zirconia (YSZ) being a common core electrolyte. Because YSZ exhibits low oxygen ion conductivity at low temperatures, traditional SOFCs typically operate at temperatures between 800°C and 1000°C to ensure sufficient ion conductivity. However, this high-temperature operation has introduced a series of technical bottlenecks, becoming a key obstacle to their commercialization. (1) Material thermal degradation: Long-term high temperature environment causes interfacial reaction, grain coarsening or phase change between electrolyte and electrode material (such as high temperature phase change of YSZ), which significantly reduces electrochemical reaction activity and structural stability. (2) Thermal stress failure: The thermal expansion coefficients of components such as electrodes, electrolytes, and interconnect materials are different. Thermal cycling at high temperatures can easily generate significant thermal stress, leading to interface peeling, microcrack initiation, or even overall structural fracture. (3) High system cost: High-temperature operation places stringent requirements on the performance of sealing materials (which must withstand extreme temperatures and chemical corrosion), interconnecting materials (which must have both high-temperature conductivity and oxidation resistance) and system structural components, leading to a surge in material and manufacturing costs; at the same time, high-temperature maintenance and system integration are difficult, further increasing the total life cycle cost.
[0004] Therefore, it is urgent to solve the problems of thermal degradation, seal failure and short lifespan of traditional SOFC stacks under high-temperature operation. Summary of the Invention
[0005] The purpose of this application is to provide a SOFC stack containing a two-stage electrolyte. By adopting a two-stage electrolyte structure, temperature gradient partitioning optimization is achieved, while taking into account high ionic conductivity and structural stability. This solves the problems of thermal degradation, sealing failure and short lifespan of traditional SOFCs under high-temperature operation.
[0006] To achieve the above objectives, this application provides an SOFC stack containing a two-stage electrolyte, comprising a high-temperature electrolyte, a transition layer, and a medium-temperature electrolyte bonded together by co-sintering; wherein The high-temperature electrolyte is made of 8 mol% yttrium-stabilized zirconium oxide film with a thickness of 98 μm to 102 μm; the medium-temperature electrolyte is made of 20 mol% samarium-doped cerium oxide (SDC) film with a thickness of 48 μm to 52 μm; the transition layer is made of a composite material of yttrium-stabilized zirconium oxide and samarium-doped cerium oxide with a thickness of 4.5 μm to 5.5 μm; the temperature ranges of the high-temperature electrolyte and the medium-temperature electrolyte are 797℃ to 713℃ and 587℃ to 603℃, respectively.
[0007] Furthermore, the yttrium-stabilized zirconia film is prepared by the following method: yttrium-stabilized zirconia powder, binder, plasticizer, and mixed solvent are weighed according to a mass ratio of (62~65):(3~4):(2~3):(30~31), stirred evenly, and then sintered; wherein the sintering temperature is 1380℃~1420℃, the holding time is 4h~6h, the heating rate is 4.0℃ / min~5.0℃ / min, the cooling rate is 2℃ / min~3℃ / min, and the sintering atmosphere is a pure oxygen atmosphere.
[0008] Furthermore, the samarium-doped cerium oxide film is prepared by the following method: samarium-doped cerium oxide, dispersant, thickener and deionized water are weighed according to the mass ratio of (58~60):(2~2.5):(0.3~0.4):(36~40), mixed evenly and then prepared by spray treatment and sintering treatment; wherein, the pressure of the spray treatment is 0.65MPa~0.7MPa, the temperature of the sintering treatment is 1280℃~1320℃, the holding time is 3h~4h, the heating rate is 3℃ / min~4℃ / min, and the cooling rate is 1℃ / min~2℃ / min.
[0009] Furthermore, the transition layer is prepared by 5 to 6 plasma spraying processes, wherein the parameters of the plasma spraying include: argon flow rate of 42 L / min to 44 L / min, hydrogen flow rate of 6 L / min to 7 L / min, power of 33 kW to 40 kW, spraying distance of 7 cm to 8 cm, and single spraying time of 7 s to 8 s; in the plasma spraying slurry, the concentration of yttrium-stabilized zirconium oxide decreases sequentially, while the concentration of samarium-doped cerium oxide increases sequentially.
[0010] Furthermore, the sintering temperature of the co-sintering treatment is 1340℃~1350℃, the holding time is 2h~4h, the heating rate is 3℃ / min~4℃ / min, and the cooling rate is 1℃ / min~2℃ / min; the atmosphere of the co-sintering treatment is a mixed atmosphere of argon and hydrogen, the volume fraction of hydrogen is 7%~8%, and the flow rate of the mixed atmosphere is 0.7L / min~0.8L / min.
[0011] Furthermore, the SOFC stack forms a temperature gradient through an alumina-based heat exchanger, which is provided with corrugated microchannels with a length of 0.25 mm to 0.3 mm and a wave height of 0.25 mm to 0.3 mm; the fuel flow rate of the alumina-based heat exchanger is 0.5 L / min to 0.7 L / min, and the air flow rate is 2 L / min to 3 L / min.
[0012] Furthermore, the SOFC stack comprises repeatedly stacked individual cells, which, from bottom to top, include interconnects, sealing layers, anodes, high-temperature electrolytes, transition layers, medium-temperature electrolytes, cathodes, sealing layers, and connectors.
[0013] Furthermore, the anode material is a nickel-doped yttrium-stabilized zirconium oxide composite material with a thickness of 490 μm to 510 μm, and the mass ratio of nickel oxide to yttrium-stabilized zirconium oxide in the nickel-doped yttrium-stabilized zirconium oxide composite material is (55~65):(35~45); the anode is prepared by automated screen printing.
[0014] Furthermore, the automated screen printing uses a 230-mesh mesh, a printing speed of 0.070 m / s to 0.8 m / s, a pressure of 0.15 MPa to 0.2 MPa, a slurry solid content of 69 wt% to 71 wt%, a sintering temperature of 1380℃ to 1420℃, a holding time of 2 h to 3 h, and a reduction atmosphere of a mixed atmosphere of hydrogen and nitrogen, a reduction temperature of 900℃ to 920℃, and a holding time of 5 h to 7 h.
[0015] Furthermore, the cathode material is La. 0.8 Sr 0.2 The composite material of MnO3 and yttrium-stabilized zirconium oxide of equal mass has a thickness of 40 μm to 60 μm; the cathode is prepared by dual-channel ultrasonic spraying.
[0016] Furthermore, the dual-channel ultrasonic spraying parameters include: power 112W~118W, frequency 130kHz~150kHz, distance 8cm~10cm, slurry solid content 53wt%~55wt%, sintering temperature 1100℃, holding time 2h~3h, and atmosphere is a mixture of nitrogen and oxygen.
[0017] Furthermore, the sealing layer is made of BaO-CaO-Al2O3-SiO2 glass ceramic, which is prepared by screen printing; the interconnect is made of 316L stainless steel with a LaCrO3 coating, which is prepared by magnetron sputtering.
[0018] In summary, this application has the following advantages: 1. The SOFC stack of this application, containing a two-stage electrolyte, utilizes the high-temperature electrolyte YSZ, which exhibits excellent oxygen ion conductivity and chemical stability in the high-temperature range, ensuring rapid ion transport at high temperatures. The medium-temperature electrolyte SDC exhibits significantly higher conductivity than YSZ in the medium-temperature range, compensating for the insufficient conductivity of YSZ in this region. This two-stage design allows the electrolyte to maintain high ion conductivity across a wide temperature range (500℃~800℃), significantly reducing ohmic polarization losses and improving battery output power and energy conversion efficiency.
[0019] 2. The fuel cell stack of this application, through the buffering effect of the transition layer, gradient-matches the thermal expansion characteristics of the high-temperature electrolyte (YSZ) and the medium-temperature electrolyte (SDC), significantly alleviating interfacial stress during the co-sintering process and reducing the risk of cracking. Furthermore, the transition layer, through the gradient composition design of the composite material, can hinder excessive element diffusion (interdiffusion between zirconium and samarium), avoiding the formation of undesirable phases and maintaining high interfacial conductivity. Moreover, the co-sintering process allows the three-layer structure to be formed in one step, resulting in tight interfacial bonding (without obvious pores or gaps), further reducing interfacial contact resistance and improving the overall mechanical strength and long-term operational reliability. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the structure of the fuel cell stack provided in an embodiment of this application.
[0021] Figure 2 This is a schematic diagram of the temperature distribution of the fuel cell stack provided in an embodiment of this application.
[0022] Figure 3 This is a schematic diagram of the performance test results of the fuel cell stack provided in an embodiment of this application.
[0023] Figure 4 This is a schematic diagram showing the relationship between the conductivity and temperature of the high-temperature electrolyte and the medium-temperature electrolyte in the fuel cell stack provided in the embodiments of this application.
[0024] Figure 5 This is a schematic diagram of the thermal stress distribution of the fuel cell stack provided in an embodiment of this application.
[0025] Figure 6 The graph shows the long-term stability test results of the fuel cell stack provided in the embodiments of this application.
[0026] Figure 7The startup and response characteristic diagram of the fuel cell stack provided in the embodiments of this application is shown in the figure. Figure 7 (a) is the startup characteristics diagram. Figure 7 (b) is the response characteristic diagram. Detailed Implementation
[0027] The principles and features of this application are described below with reference to embodiments. The examples are for illustrative purposes only and are not intended to limit the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0028] To overcome the limitations of traditional SOFC stacks in terms of thermal degradation, seal failure, and short lifespan under high-temperature operation, intermediate-temperature SOFCs (operating temperature 500℃~700℃) have become a research hotspot in recent years. Lowering the operating temperature can effectively alleviate thermal stress, reduce material degradation, and reduce the performance requirements of sealing and interconnecting materials, thereby improving system durability and economy. However, intermediate-temperature SOFCs face new challenges, such as (1) insufficient electrolyte conductivity: the oxygen ion conductivity of YSZ at 500℃~700℃ decreases significantly (only 1 / 10~1 / 5 of that at high temperatures), resulting in a sharp increase in ohmic impedance and a significant reduction in stack output power. For example, (2) material matching problems: to improve intermediate-temperature conductivity, it can be achieved by doping with intermediate-temperature electrolyte materials such as cerium oxide, but the interface between it and the traditional electrode or YSZ layer is prone to high resistance layer due to thermal expansion coefficient mismatch, which increases the interface impedance. (3) For example, poor system synergy: The thermal management strategies of existing medium-temperature SOFCs mostly follow the high-temperature system design, which is difficult to adapt to the temperature gradient distribution in the medium temperature range, resulting in local thermal stress concentration; at the same time, the problems of decreased electrode catalytic activity at medium temperature, sealing materials (traditional high-temperature sealing materials are not sealing enough at medium temperature, and the development of new materials is lagging behind) and dynamic response performance (slow start-up speed and poor adaptability to load changes) are also quite prominent. For another example, (4) insufficient long-term stability: Under medium temperature conditions, the ion migration behavior of electrolytes, carbon deposition of electrodes and sulfur poisoning effects are more difficult to control, resulting in a faster performance degradation rate of the stack after long-term operation (usually the degradation rate is >15% after 1000 hours).
[0029] Therefore, the main objective of this application is to develop a SOFC stack design that can balance high ionic conductivity, structural stability and system synergy in the mid-temperature range of 500℃ to 700℃, in order to solve the thermal degradation problem of traditional high-temperature systems and the performance bottleneck of existing mid-temperature solutions.
[0030] Based on this, this application provides a SOFC stack containing a two-stage electrolyte, employing a two-stage structure composed of a high-temperature electrolyte (such as YSZ) and a medium-temperature electrolyte (such as SDC). Through temperature gradient partitioning optimization, a synergistic improvement in high ionic conductivity and structural stability is achieved. Furthermore, this application effectively reduces thermal stress and interface resistance through reasonable design of electrolyte thickness and material composition, as well as optimized thermal management strategies, thereby improving the performance and lifespan of the stack.
[0031] Specifically, it includes a high-temperature electrolyte, a transition layer, and a medium-temperature electrolyte bonded together through co-sintering; wherein the high-temperature electrolyte is made of 8 mol% yttrium-stabilized zirconia film (8YSZ) with a thickness of 98 μm to 102 μm; the medium-temperature electrolyte is made of 20 mol% samarium-doped cerium oxide film (SDC) with a thickness of 48 μm to 52 μm; the transition layer is made of a composite material of yttrium-stabilized zirconia and samarium-doped cerium oxide with a thickness of 4.5 μm to 5.5 μm; the temperature ranges of the high-temperature electrolyte and the medium-temperature electrolyte are 797℃ to 713℃ and 587℃ to 603℃, respectively.
[0032] In the above scheme, the high-temperature electrolyte section uses 8YSZ (Y2O3 doped with ZrO2, purity 99.95%, Tosoh), which is suitable for the high-temperature region of the fuel cell stack (around 800℃), ensuring high oxygen ion conductivity (approximately 0.1 S / cm at 800℃) and chemical stability; the medium-temperature electrolyte section uses SDC (SDC, Sm 0.2 Ce 0.8 O 1.9 (99.9% purity, Fuel Cell Materials), suitable for the mid-temperature range (around 600°C) of fuel cells, providing excellent mid-temperature conductivity (approximately 0.05 S / cm at 600°C) and thermal shock resistance. The high-temperature electrolyte and mid-temperature electrolyte are combined through a co-sintering process, ensuring an interfacial resistivity below 0.01 Ω·cm. 2 Simultaneously, the thermal expansion coefficient matching is optimized through a transition layer (YSZ: 10.5×10). -6 K -1 SDC: 12.0×10 - 6 K -1 This reduces interfacial stress.
[0033] Preferably, the purity of 8YSZ is >99.95%, and the powder specific surface area is 8m². 2 / g~10m 2 / g, the cationic conductivity at 800℃ is 0.102S / cm~0.110S / cm, and the coefficient of thermal expansion is 10.4×10 -6 K -1~10.6×10 -6 K -1 The purity of SDC is >99.9%, and the powder specific surface area is 10m². 2 / g~12m 2 / g, the cationic conductivity at 600℃ is 0.049S / cm~0.055S / cm, and the coefficient of thermal expansion is 11.8×10 -6 K -1 ~12.2×10 -6 K -1 .
[0034] As an optional embodiment of this application, the yttrium-stabilized zirconia film is prepared by casting, including the following steps: weighing yttrium-stabilized zirconia powder, binder, plasticizer and mixed solvent in a mass ratio of (62~65):(3~4):(2~3):(30~31) to prepare a slurry, stirring it evenly and then sintering it to obtain the film.
[0035] In a specific embodiment, the sintering temperature is 1380℃~1420℃, the holding time is 4h~6h, the heating rate is 4℃ / min~5℃ / min, the cooling rate is 2℃ / min~3℃ / min, and the sintering atmosphere is a pure oxygen atmosphere (O2 purity 99.999%, flow rate 0.25L / min). Preferably, in the slurry, the mass fractions of yttrium-stabilized zirconia powder, binder, plasticizer, and mixed solvent are 63wt%, 3.8wt%, 2.2wt%, and 31wt%, respectively. The binder is preferably polyvinyl alcohol, the plasticizer is preferably butanediol, and the mixed solvent is preferably an equal volume mixture of ethanol and acetone with a concentration of 31wt%. Preferably, the stirring speed of the slurry is 400rpm~600rpm, the stirring time is 7h~10h, and the viscosity of the slurry is 1700mPa·s~1800Pa·s.
[0036] As an optional embodiment of this application, the samarium-doped cerium oxide film is prepared by centrifugal spray drying, including the following steps: samarium-doped cerium oxide, dispersant, thickener and deionized water are weighed according to the mass ratio (58~60):(2~2.5):(0.3~0.4):(36~40) to prepare a slurry, which is then mixed evenly and prepared by spray treatment and sintering treatment.
[0037] In a specific embodiment, the centrifugal spray treatment pressure is 0.65 MPa to 0.7 MPa, the sintering treatment temperature is 1280℃ to 1320℃, the holding time is 3h to 4h, the heating rate is 3℃ / min to 4℃ / min, the cooling rate is 1℃ / min to 2℃ / min, and the sintering atmosphere is air. Preferably, the mass fractions of samarium-doped cerium oxide, dispersant, thickener, and deionized water in the slurry are 59wt%, 2.3wt%, 0.4wt%, and 38.3wt%, respectively. The dispersant is preferably polyethylene glycol, the thickener is preferably ammonium polyacrylate, and the pH value of the slurry is preferably 7.3 to 7.7.
[0038] As an optional embodiment of this application, the transition layer is obtained by spraying Ar / H2 plasma onto the high-temperature electrolyte layer 5 to 6 times and then co-sintering.
[0039] In a specific embodiment, the parameters of the plasma spraying include: argon flow rate of 42 L / min to 44 L / min, hydrogen flow rate of 6 L / min to 7 L / min, power of 33 kW to 40 kW, spraying distance of 7 cm to 8 cm, and single spraying time of 7 s to 8 s; in the plasma spraying slurry, the concentration of yttrium-stabilized zirconium oxide decreases sequentially, while the concentration of samarium-doped cerium oxide increases sequentially. Preferably, the total thickness of the transition layer is 4.5 μm to 5.5 μm.
[0040] In a specific implementation, the five Ar / H2 plasma spraying processes sequentially include: the first spraying with YSZ slurry for 8s~12s; the second spraying with a mixed slurry of YSZ:SDC=75:25 (by mass) for 8s~12s; the third spraying with a mixed slurry of YSZ:SDC=50:50 for 8s~12s; the fourth spraying with a mixed slurry of YSZ:SDC=25:75 for 8s~12s; and the fifth spraying with SDC slurry for 8s~12s, thus completing the five spraying processes and forming a gradient transition layer.
[0041] In a specific implementation, the six Ar / H2 plasma spraying processes sequentially include: the first spraying with YSZ slurry for 8s~12s; the second spraying with a mixed slurry of YSZ:SDC=80:20 (by mass) for 8s~12s; the third spraying with a mixed slurry of YSZ:SDC=60:40 for 8s~12s; the fourth spraying with a mixed slurry of YSZ:SDC=40:60 for 8s~12s; the fifth spraying with a mixed slurry of YSZ:SDC=20:80 for 8s~12s; and the sixth spraying with SDC slurry for 8s~12s. These six spraying processes complete the process, forming a gradient transition layer.
[0042] As an optional embodiment of this application, the sintering temperature of the co-sintering treatment is 1340℃~1350℃, the holding time is 2h~4h, the heating rate is 3℃ / min~4℃ / min, and the cooling rate is 1℃ / min~2℃ / min; the atmosphere of the co-sintering treatment is a mixed atmosphere of argon and hydrogen, the volume fraction of hydrogen is 7%~8%, and the flow rate of the mixed atmosphere is 0.7L / min~0.8L / min.
[0043] As an optional embodiment of this application, the SOFC stack forms a temperature gradient through an alumina-based heat exchanger. The alumina-based heat exchanger is equipped with corrugated microchannels with a length of 0.25 mm to 0.3 mm, a wave height of 0.25 mm to 0.3 mm, and a width of 0.4 mm to 0.5 mm. The fuel flow rate of the alumina-based heat exchanger is 0.5 L / min to 0.7 L / min, the air flow rate is 2 L / min to 3 L / min, the fuel pressure drop is 400 Pa to 500 Pa, and the air pressure drop is 800 Pa to 1000 Pa. Preferably, the temperature is monitored using 12-point K-type thermocouples (1.5 cm spacing, accuracy ±0.8 °C) and an infrared thermometer (0.1 °C resolution), with a temperature difference of 10 ± 1 °C / cm.
[0044] As an optional implementation of this application, such as Figure 1 As shown, the SOFC stack comprises repeatedly stacked individual cells. From bottom to top, each individual cell includes an interconnect, a sealing layer, an anode, a high-temperature electrolyte, a transition layer, a medium-temperature electrolyte, a cathode, another sealing layer, and a connector. Preferably, the number of individual cells is 20 to 25 layers, processed to a size of 10cm using laser cutting (50W power, ±0.05mm accuracy). 2 ×10cm 2 After reassembly, the total power is 540W~560W.
[0045] In the above scheme, the anode uses a Ni-YSZ composite material to provide high electrocatalytic activity; the cathode uses La... 0.8 Sr 0.2 MnO3-YSZ composite material (LSM-YSZ) is used to improve oxygen reduction reaction efficiency. The fuel cell stack uses thermal management design to create a temperature gradient, with the high-temperature zone near the fuel inlet (approximately 800°C) and the medium-temperature zone near the air outlet (approximately 600°C). Temperature distribution is optimized through ceramic heat exchangers and airflow regulation.
[0046] As an optional embodiment of this application, the anode material is a nickel-doped yttrium-stabilized zirconium oxide composite material (NiO-YSZ) with a thickness of 490μm~510μm. The mass ratio of nickel oxide to yttrium-stabilized zirconium oxide in the nickel-doped yttrium-stabilized zirconium oxide composite material is (55~65):(35~45). The anode is prepared by automatically screen printing a paste onto the surface of a high-temperature electrolyte and then sintering it.
[0047] In a specific embodiment, the automated screen printing uses a 230-mesh mesh, a printing speed of 0.070 m / s to 0.8 m / s, a pressure of 0.16 MPa to 0.19 MPa, a slurry with a solid content of 69 wt% to 71 wt%, a viscosity of 2100 mPa·s to 2500 mPa·s, a heating rate of 4℃ / min to 5℃ / min, a sintering temperature of 1380℃ to 1420℃, and a holding time of 2 h to 3 h. Preferably, the automatic screen printing uses a mixed atmosphere of hydrogen and nitrogen (H2: 12 vol%, flow rate 0.7 L / min), a reduction temperature of 900℃ to 920℃, and a holding time of 5 h to 7 h.
[0048] As an optional embodiment of this application, the cathode material is La. 0.8 Sr 0.2 The composite material of MnO3 and yttrium-stabilized zirconium oxide of equal mass has a thickness of 40μm~60μm; the cathode is prepared by spraying slurry onto the surface of a medium-temperature electrolyte through dual-channel ultrasonication, followed by sintering.
[0049] In a specific embodiment, the dual-channel ultrasonic spraying parameters include: power 110W~120W, frequency 130kHz~150kHz, distance 8cm~10cm, slurry solid content 50wt%~60wt%, slurry viscosity 900mPa·s~1000mPa·s, sintering temperature 1080℃~1120℃, holding time 2h~3h, atmosphere is a mixed atmosphere of nitrogen and oxygen (O2: 22vol%), and heating rate is 3℃ / min~5℃ / min.
[0050] As an optional embodiment of this application, the sealing layer is made of BaO-CaO-Al2O3-SiO2 glass ceramic (softening point 610℃~620℃, viscosity 10). 3.8 The sealing layer (Pa·s) is prepared by screen printing. Preferably, the thickness of the sealing layer is 0.1 mm to 0.2 mm. As an optional embodiment of this application, the interconnect is made of 316L stainless steel with a LaCrO3 coating (coating thickness of 5μm~10μm) and a contact resistance of 0.025Ω·cm. 2~0.03Ω·cm 2 The LaCrO3 coating was prepared by magnetron sputtering.
[0051] In summary, firstly, this application employs a two-stage electrolyte structure, with gradient optimization performed within the temperature range of 500℃ to 800℃. YSZ provides high oxygen ion conductivity in the high-temperature region, while SDC provides excellent conductivity and thermal shock resistance in the mid-temperature region. The two electrolyte stages are combined through a co-sintering process, with a YSZ-SDC gradient layer introduced at the interface to reduce thermal expansion mismatch (YSZ: 10.5 × 10⁻⁶). -6 K -1 SDC: 12.0×10 -6 K -1 This allows the interface resistance to be controlled within 0.007 ± 0.001 Ω·cm. 2 The following points are key to understanding the advantages of this application. First, compared to the traditional single YSZ electrolyte (conductivity of approximately 0.02 S / cm at 600℃), the two-stage electrolyte structure of this application significantly improves mid-temperature performance, avoiding the problems of high-temperature phase transition and insufficient mid-temperature conductivity. Second, this application creates an internal temperature gradient in the stack through thermal management (alumina-based ceramic heat exchanger and airflow control). The high-temperature zone (fuel inlet, 800±10℃) matches the optimal conductivity temperature of YSZ, while the mid-temperature zone (air outlet, 600±10℃) matches the stable operating temperature of SDC. The heat exchanger uses Al2O3-based ceramic (thermal conductivity 18 W / m·K~22 W / m·K), and the fuel flow rate and air flow rate are controlled to precisely maintain the temperature difference at 10±1℃ / cm. Compared to the single temperature distribution of traditional SOFCs (temperature difference >20℃ / cm), the design of the internal temperature gradient in the stack can optimize thermal stress (maximum 82±3 MPa), thereby improving structural stability. Thirdly, this application achieves a synergistic improvement in performance and lifespan through the high conductivity of YSZ and the structural stability of SDC. YSZ ensures high power output of the fuel cell stack (1.27W / cm²) in the high-temperature region. 2 At 800℃, SDC enhances thermal cycling resistance (200 cycles, 500℃~800℃, attenuation 2.2±0.3%) in the mid-temperature range through low porosity (2.5±0.2%) and uniform grain size (0.8±0.2μm). The interface gradient layer and co-sintering process (bonding strength 68±4MPa) further reduce interfacial resistance and thermal stress. Long-term testing (30,000 hours, 650℃, 0.5A / cm) 2 The degradation rate was only 4.2±0.1%, which is better than that of traditional SOFC (10±1.5%). Compared with traditional composite electrolytes (interface resistance >0.02Ω·cm²), this application can significantly improve efficiency and lifetime.
[0052] The technical solutions described above in this application will be explained in detail below with reference to specific embodiments.
[0053] Example 1 This embodiment provides a high-temperature electrolyte for an SOFC stack containing a two-stage electrolyte, which is prepared by the following method: S101. 8 mol% yttrium-stabilized zirconium oxide (8YSZ, Y₂O₃ doped with ZrO₂, purity 99.95%, Tosoh Corporation) powder was selected as the high-temperature electrolyte raw material, with a powder specific surface area (BET) of 9.5 m². 2 / g, flexural strength 340MPa, powder cost 300CNY / kg. The powder is spray-granulated to a particle diameter of 20μm to improve flowability, and the BET specific surface area is determined by nitrogen adsorption method.
[0054] S102, the slurry formulation includes: YSZ powder (63.5wt%), polyvinyl alcohol binder (3.7wt%), butanediol plasticizer (2.3wt%), and ethanol / acetone mixed solvent (30.5wt%, ethanol / acetone = 1:1 v / v). The slurry was mixed using a planetary mixer (650 rpm, 8.5 hours) to a viscosity of 1720 mPa·s (Brookfield viscometer, 20 rpm), and then filtered through a 200-mesh sieve (75 μm pore size) to remove impurities. A high-precision casting machine (roller speed 0.175 m / min, roller spacing 0.275 mm, constant temperature 25℃, humidity 40%) was used to prepare a 100 μm thick YSZ film.
[0055] S103 and YSZ films were leveled using a double-sided scraper (accuracy ±0.5μm) and sintered at 1400℃ for 4.8 hours in a high-purity oxygen atmosphere (O2 purity 99.999%, flow rate 0.27L / min, pressure 0.1MPa). The heating rate was 4.8℃ / min, and the cooling rate was 2.3℃ / min. The resulting high-temperature electrolyte had a porosity of 4.0±0.15%, a grain size of 1.3μm, and a flexural strength of 300MPa~350MPa. The sintering furnace was equipped with a dual-channel infrared thermometer (accuracy ±0.8℃, response time 0.1 seconds) to monitor temperature uniformity, and the furnace atmosphere was monitored in real time using an oxygen analyzer (accuracy ±0.01%).
[0056] S104. The prepared high-temperature electrolyte and intermediate materials are tested, including: 1): The powder particle size was determined by laser particle size analyzer (Malvern Mastersizer 3000, repeatability ±0.5%), and the results showed that D50 = 0.47 ± 0.01 μm and D90 < 0.9 μm.
[0057] 2): The surface roughness of the thin film was examined by atomic force microscopy (Bruker Dimension Icon, scanning range 10μm×10μm), and the roughness Ra < 7.5nm.
[0058] 3): Conductivity was tested using the DC four-probe method (Keithley 2635B, 10mA current, error <0.2%). Figure 4 The conductivity of YSZ at 800℃ is shown to be 0.106 S / cm, which is approximately 17.8% higher than the conductivity of traditional YSZ (0.09 S / cm). Specifically, Figure 4 The conductivity curves for 8YSZ and SDC continuously cover the temperature range of 500℃ to 1000℃. 8YSZ exhibits a conductivity of 0.106±0.004 S / cm in the high-temperature region (800℃), while SDC exhibits a conductivity of 0.053±0.002 S / cm in the mid-temperature region (600℃). These typical performance points are marked on the curves. The conductivity of conventional YSZ at 600℃ (0.02 S / cm) serves as an independent reference point, not directly related to the curves, but used to demonstrate the conductivity advantages of this application. Figure 4 The synergistic conductivity advantage of the two electrolyte segments under optimized temperature gradient (temperature difference 9.5 ± 0.5 °C / cm) was verified, supporting the mid-temperature high performance of the fuel cell stack (1.29 W / cm). 2 ).
[0059] 4) The structure was confirmed by X-ray diffraction (Bruker D8 Advance, Cu Kα, 2θ=20°~80°, scanning rate 1.5° / min). YSZ is a cubic phase and there are no impurities or tetragonal phases (detection limit <0.5wt%).
[0060] 5) The porosity of YSZ was determined by the Archimedes method (accuracy ±0.1%), and the porosity was found to be 4.0 ± 0.15%.
[0061] Example 2 This embodiment provides a medium-temperature electrolyte and transition layer for an SOFC stack containing a two-stage electrolyte, which is prepared by the following method: S201, using 20 mol% samarium-doped cerium oxide (SDC, Sm) 0.2 Ce 0.8 O 1.9 The powder (99.9% purity, from Fuel Cell Materials) is used as a raw material for a medium-temperature electrolyte, with a specific surface area of 11.5 m². 2 The powder has a strength of 280 MPa and a flexural strength of 280 MPa, with a powder cost of 315 CNY / kg. The powder is granulated using ultrasonication at a frequency of 20 kHz to obtain particles with a diameter of 18 μm to optimize flowability.
[0062] S202, the slurry formulation includes: SDC powder (59.5wt%), polyethylene glycol dispersant (2.2wt%), ammonium polyacrylate thickener (0.35wt%), and deionized water (38wt%, conductivity <0.1μS / cm). The pH of the slurry is 7.5 (adjusted by titration with 0.1M NH4OH). The slurry is treated with ultrasound (40kHz, 12 minutes, power 200W) to eliminate bubbles and improve dispersibility.
[0063] S203. A centrifugal spray dryer (nozzle diameter 0.4 mm, inlet air temperature 188℃, outlet air temperature 90℃, spray pressure 0.67 MPa, centrifugal speed 12000 rpm) was used to prepare an SDC film with a thickness of 50 μm. The SDC film was then sintered at 1300℃ for 3.8 hours in a filtered air atmosphere (0.1 μm filter, humidity <5 ppm). The heating rate was 3.8℃ / min, and the cooling rate was 1.7℃ / min. The porosity of the sintered SDC film was 2.3 ± 0.1%.
[0064] S204, the interface, i.e. the transition layer, adopts a 4.7μm thick YSZ-SDC gradient layer (six-step spraying, ratios 100:0, 80:20, 60:40, 40:60, 20:80, 0:100, each step spraying for 7.5 seconds, with the spraying power increasing by 0.5kW step by step).
[0065] S205 and SDC are deposited on the surface of the transition layer by plasma spraying, and then the high-temperature electrolyte, the transition layer and the medium-temperature electrolyte are co-sintered.
[0066] The plasma spraying parameters include: Ar / H2 plasma spraying, Ar flow rate of 43 L / min, H2 flow rate of 6.5 L / min, power of 33.5 kW, spraying distance of 7.5 cm, and deposition efficiency of 91%.
[0067] The co-sintering parameters included: sintering at 1345℃ for 3 hours, under an Ar / H2 atmosphere (H2: 7.5 vol%, flow rate 0.48 L / min, pressure 0.12 MPa), a heating rate of 3.3℃ / min, a cooling rate of 1.5℃ / min, and an interfacial bonding strength of 70 ± 3 MPa and an interfacial resistance of 0.0065 ± 0.0003 Ω·cm, as determined by micro-tensile testing. 2 This yields an electrolyte structure containing a medium-temperature electrolyte, a transition layer, and a high-temperature electrolyte.
[0068] S206. Perform performance tests on the prepared intermediate-temperature electrolyte, including: 1): SDC doping was verified by X-ray photoelectron spectroscopy (XPS, Thermo Fisher ESCALAB 250Xi, Sm / Ce=0.255±0.005, energy resolution of 0.05eV).
[0069] 2): The interface was analyzed by high-resolution transmission electron microscopy (HRTEM, FEI Titan G2, resolution 0.1nm). The thickness of the diffusion layer was 1.65μm, with no grain boundary defects or microcracks.
[0070] 3): The resistance was measured by AC impedance spectroscopy (Solartron 1260, frequency 0.1Hz~1MHz, amplitude 10mV), and the resistance was 0.0065±0.0003Ω·cm. 2 .
[0071] 4): The film density was confirmed by X-ray reflectance (XRR, accuracy ±0.1%), and the density was >97%. Figure 1 The YSZ-SDC dual-layer structure and gradient layer design are showcased, highlighting the structural features of interface optimization. Figure 1 The image clearly shows two electrolyte sections: a high-temperature electrolyte section and a medium-temperature electrolyte section, as well as a transition layer at the YSZ-SDC interface. It also shows that the anode and cathode are located on opposite sides of the electrolyte, while the interconnects and sealing layer ensure the structural integrity and hermeticity of the stack.
[0072] Example 3 This embodiment provides an anode and cathode of an SOFC stack containing a two-stage electrolyte, including the following steps: S301. The anode is a NiO-YSZ composite material (Ni content 40 vol% after reduction), with NiO:YSZ = 60:40 wt%. Both NiO and YSZ powders have a particle size of 0.5 μm and a purity > 99.9%, respectively. The material cost is 140 CNY / kg. The powder is ball-milled at 400 rpm for 10 hours using ZrO2 balls at a ball-to-powder ratio of 10:1 to optimize dispersibility, and then prepared into a slurry. The slurry has a solid content of 70 wt% and a viscosity of 2250 mPa·s (achieved through high-shear mixing at 2200 rpm for 12 minutes). 0.5 wt% defoamer (polysiloxane) is added to reduce bubbles.
[0073] S302, using an automated screen printing machine (230 mesh, 60μm aperture, speed 0.075m / s, pressure 0.175MPa, ambient humidity 45%), the paste is coated onto the other side of the YSZ high-temperature electrolyte (e.g., ...). Figure 1As shown, the anode slurry and transition layer slurry are coated on both sides of the YSZ high-temperature electrolyte, with a thickness of 500 μm.
[0074] After printing, the coating is cured by infrared drying (80℃, 10 minutes), and then sintered at 1400℃ in an air atmosphere (humidity <8ppm, oxygen content 21vol%) for 2.8 hours with a heating rate of 5.0℃ / min.
[0075] After sintering and solidification, a reduction treatment was carried out in a H2 / N2 mixed gas (H2: 13 vol%, flow rate 0.75 L / min, pressure 0.15 MPa) and held at 910℃ for 6 hours. The resulting anode had a porosity of 33% and a pore size of 1.7 μm (X-ray micro-CT, spatial resolution 0.5 μm).
[0076] S303. The prepared anode was tested, and its H2 oxidation current density was 0.60 ± 0.01 A / cm. 2 At 0.7V (800℃, potentiostatic method, Gamry Reference 3000), the polarization resistance is 0.125±0.003Ω·cm. 2 (EIS, 10 MHz to 100 kHz, temperature 650°C to 800°C). Tested for 10,000 hours (0.5 A / cm). 2 After 650℃, the agglomeration rate was <3.2% and the carbon deposition was <0.07wt% (SEM and EDS, magnified 2000 times, C element content <0.5at%). Figure 5 The thermal stress optimization of the porous structure is demonstrated (maximum stress 80±2 MPa), with the thermal stress gradually decreasing from the high-stress region near the fuel inlet (maximum 80±1 MPa) to the low-stress region near the air outlet (approximately 50 MPa). Compared to conventional SOFC stacks (thermal stress >10 MPa), this application reduces the maximum thermal stress to 80±1 MPa and the shear stress to below 50 MPa through optimization of the two-stage electrolyte structure and thermal management, thereby improving structural stability. Figure 5 The thermal stress optimization effect of this application was directly verified, supporting the long-term stability of the fuel cell stack (4.2 ± 0.1% decay rate over 30,000 hours).
[0077] S304, cathode selected: La 0.8 Sr 0.2The MnO3(LSM)-YSZ composite material (composite ratio 50wt%:50wt%, LSM powder particle size 0.4μm, YSZ powder particle size 0.5μm, purity 99.8%) has a material cost of 210 CNY / kg. The mixed powder was ball-milled (350 rpm, 14 hours, ethanol medium) to ensure homogeneity. The mixed powder was then prepared into a slurry with a solid content of 54wt% and a viscosity of 920 mPa·s, prepared by ball milling (320 rpm, 13 hours). 0.3wt% ammonium polycarboxylate dispersant was added to the slurry.
[0078] S305 uses dual-channel ultrasonic spraying (power 115W, frequency 140kHz, spraying distance 9cm, nozzle diameter 0.5mm) to deposit slurry on the surface of SDC medium-temperature electrolyte, with a thickness of 48μm.
[0079] The coating was cured by hot air drying (90℃, 8 minutes) after spraying, sintered at 1100℃ for 2.5 hours, under an O2 / N2 atmosphere (O2: 23 vol%, flow rate 0.5 L / min, pressure 0.1 MPa) and a heating rate of 4.0℃ / min. The resulting cathode had a porosity of 28±0.3% and a pore size of 0.65±0.1 μm (mercury pressure method, pressure 0.1 MPa~400 MPa).
[0080] S306. The prepared cathode is subjected to performance testing, including: oxygen reduction current density 0.36±0.01A / cm. 2 at 0.8V (600℃, potentiostatic method), polarization resistance 0.075±0.003Ω· / cm 2 (EIS, 600℃~800℃). After 120 thermal cycles (500℃~800℃, heating rate 12±1℃ / min), the resistivity increased by 1.4±0.1%, and Sr segregation was <1.8% (EDS and XPS, Sr / La ratio <0.02). Figure 3 The cathode's performance at 600℃ was demonstrated (0.86 W / cm²). 2 ).
[0081] Example 4 This embodiment provides an SOFC stack containing a two-stage electrolyte, which includes the electrolytes prepared in Examples 1 and 2, and the cathode and anode prepared in Example 3.
[0082] Specifically, SOFC stacks are prepared using the following methods: The S401 fuel cell stack adopts a flat design, stacking 24 layers of individual cells (including the stacked cells), divided into 6 modules (each module has 4 layers, 100W), with a total power of 600W. Each cell is processed to an area of 10cm² using laser cutting (power 50W, accuracy ±0.05mm). 2 ×10cm 2 (Effective area 95±1cm) 2 ).
[0083] S402, the battery compartment is sealed with BaO-CaO-Al2O3-SiO2 glass-ceramic seal (softening point 610℃, viscosity 10). 3.8 Pa·s, coefficient of thermal expansion 11.0×10 -6 K -1 The cost is 70 CNY / kg. The sealing layer is coated by high-precision screen printing (300 mesh, 50 μm aperture, 0.175 mm thickness, printing speed 0.1 m / s). The resulting sealing layer can withstand a pressure of 0.28 ± 0.01 MPa and 200 heat cycles (helium leak detection, leak rate <0.0025 sccm / cm, pressure 0.2 MPa). Figure 7 This demonstrates the stability of the sealing structure during rapid startup. Figure 7 (a) indicates the startup characteristics, showing that the fuel cell stack can be heated from room temperature (25°C) to 600°C in just 12.8 ± 0.3 minutes, which is better than traditional SOFC (>20 minutes). Figure 7 (b) shows the response characteristics, indicating the effect of a sudden load change (0.3 A / cm). 2 ~0.8A / cm 2 The response time is 1.45 ± 0.05 seconds, which is better than the traditional SOFC (>3 seconds).
[0084] S403, the interconnect is 316L stainless steel with a LaCrO3 coating (7.5μm coating, obtained by magnetron sputtering deposition, power 2.5kW, deposition rate 0.25μm / min, cost 350CNY / m). 2 The contact resistance of the interconnect is 0.026 ± 0.001 Ω·cm. 2 (Four-probe method, pressure 0.5MPa).
[0085] The S404 end plate is made of 316L stainless steel (thickness 4.8mm, cost 140CNY / kg, tensile strength 550MPa), and is isolated by ZrO2 ceramic gaskets (thickness 0.95mm, cost 210CNY / kg, thermal conductivity 2W / m·K). Its compressive force is 0.5MPa (obtained by servo press test, torque accuracy ±0.05N·m).
[0086] S405 assembly is completed through an automated production line (positioning accuracy ±10μm, cycle time 30 seconds / battery), with a yield rate >98%.
[0087] The S406 uses an Al2O3-based ceramic heat exchanger (thermal conductivity 21 W / m·K, corrugated microchannels 0.27 mm, wave height 0.26 mm, channel spacing 0.5 mm, cost 700 CNY / kg), achieving a heat exchange efficiency of 20.5 ± 0.5%. The fuel (H2) flow rate is 0.6 L / min, and the air flow rate is 2.3 L / min, controlled by a mass flow meter (accuracy ± 0.3%, response time 0.1 seconds). The pressure drop in the fuel channel is 430 Pa, and the pressure drop in the air channel is 880 Pa (CFD optimization, 5 million meshes, residual < 10). -6 The flow channels employ a serpentine fuel channel (2 mm wide, 1 mm deep) and parallel air channels (1.5 mm wide, 0.8 mm deep), fabricated via laser micromachining (accuracy ±5 μm). Temperature is monitored using 15 K-type thermocouples (1.2 cm spacing, accuracy ±0.5℃, response time 0.2 seconds) and an infrared thermometer (FLIR T650sc, resolution 0.03℃, frame rate 30 Hz), with a temperature difference of 9.5℃ / cm, a high-temperature range of 805℃, and a medium-temperature range of 600℃. Thermal stress is optimized using finite element analysis (Abaqus, mesh accuracy 0.05 mm, material model considering nonlinear elasticity), with a maximum thermal stress of 80 ± 1 MPa and shear stress < 50 MPa. The heat exchanger is fixed with ceramic adhesive (bonding strength 10 MPa) and can withstand temperatures up to 1000℃. Figure 2 The temperature distribution curve was shown, verifying the temperature difference control. Figure 5 The thermal stress distribution is shown, highlighting the structural stability. Figure 2 The temperature gradient distribution along the fuel and air flow directions inside the fuel cell stack is shown in a two-dimensional heat map. The horizontal axis represents the stack length (from fuel inlet to air outlet), and the vertical axis represents the stack height (from anode to cathode). The temperature gradually decreases from the high-temperature zone at the fuel inlet (805±5℃) to the medium-temperature zone at the air outlet (595±5℃), with the temperature difference controlled at 9.5±0.5℃ / cm, verifying the effectiveness of the thermal management design. Figure 2 The temperature distribution is displayed intuitively using a color gradient (red represents high temperature, blue represents low temperature), and key temperature points (805℃, 700℃, 595℃) and temperature difference values are marked. Figure 2 The synergistic effect of ceramic heat exchangers (microchannel 0.27±0.005mm) and airflow regulation (fuel 0.58±0.02L / min, air 2.3±0.05L / min) highlights the advantages of this application in terms of temperature gradient optimization and structural stability (thermal stress 80±1MPa).
[0088] The performance of the SOFC stack prepared in this embodiment was tested, including: (1) Electrochemical performance Tests were conducted at 600℃, 650℃, 700℃, and 800℃. Figure 3 As shown, the power densities are 0.86 ± 0.01 W / cm². 2 1.00±0.01W / cm 2 1.10±0.01W / cm 2 and 1.29±0.01W / cm 2 The open-circuit voltage is 1.08±0.005V, and the ohmic resistance is 0.085±0.003Ω·cm. 2 The polarization resistance is 0.065 ± 0.003 Ω·cm. 2 (Gamry Reference 3000, scan rate 0.5mV / s, current range 0-2A / cm) 2 ).
[0089] Fuel utilization rate was 80±0.5%, air utilization rate was 33±0.5%, and thermal efficiency was 68±0.5% (based on lower heating value, error ±0.2%). The test was verified by constant flow / constant pressure mode (repeated 3 times, standard deviation <0.5%), and the environment was controlled in a constant temperature chamber (temperature fluctuation ±0.5℃, humidity <10%). Figure 3 The IV and power density curves are shown, compared to the traditional YSZ stack (600℃: 0.48W / cm²). 2 The increase was 79.2 ± 2%.
[0090] (2) Long-term stability like Figure 6 As shown, the fuel cell stack passed a 30,000-hour accelerated aging test (650℃, 0.5A / cm). 2 After acceleration factor 1.2, the decay rate was 4.2±0.1%, significantly lower than that of the traditional YSZ stack (10±1.5%). The electrolyte showed no phase change (XRD, 2θ=20°~80°, peak position deviation <0.02°), electrode grain growth was <6.5% (TEM, resolution 0.1nm, grain size statistics >100 grains), and cathode Sr segregation was <1.4% (XPS, Sr 3d peak integration error <0.5%). After three simulated shutdowns (each <1 hour), the performance recovery rate was >99.8%. Figure 6 The decay rate curve (0-30000 hours, in 2500-hour increments) is shown, which is superior to that of traditional SOFC (10±1.5%).
[0091] (3) Dynamic response Start-up time: 12.8 ± 0.3 minutes (heating power: 3.2 ± 0.1 kW, heating rate: 22 ± 1 °C / min, electric heater efficiency: 95 ± 1%), load change (0.3 A / cm). 2 ~0.8A / cm 2 Step 0.05A / cm 2 Response time 1.45±0.05 seconds (PID controller, response frequency 12±1Hz, overshoot <0.5%). After 300 thermal cycles (500℃~800℃, heating rate 12±0.5℃ / min, holding time 30 minutes), the decay is 1.9±0.1%, and the sealing leakage rate is <0.002sccm / cm (helium leak detection, 0.25MPa). Figure 7 Display startup and response curves to verify fast dynamic performance.
[0092] (4) Fuel adaptability It supports H2 / CH4 mixed fuels (CH4 content ≤50±2%), with a reforming efficiency of 96.5±0.5% (steam / carbon ratio 1.7±0.05, Ni-YSZ catalysis, reaction temperature 800±10℃). Resistant to H2S (250ppm, 5000 hours, attenuation <2.5%); Resistant to CO (400ppm, 4000 hours, no poisoning, Ni surface C content <0.3at%).
[0093] CH4 reforming was monitored by online gas chromatography (GC, Agilent 7890B, resolution 0.1ppm), with a CO / CO2 ratio <0.05. Figure 6 Showing fuel adaptability data (H2S, CH4 test curves). The fuel cell stack operates at 650℃ and 0.5 A / cm². 2 Performance degradation under load and fuel adaptability. After 30,000 hours of operation, the performance degradation rate of the fuel cell stack was 4.2 ± 0.1%, significantly lower than that of the conventional YSZ fuel cell stack (10 ± 1.5%). Fuel adaptability tests showed that the fuel cell stack performed well under CO tolerance (400 ppm, 4000 hours, degradation < 2.5%) and CH4 reforming (≤ 50%, 5000 hours, degradation < 2.5%) conditions.
[0094] (5) Environmental adaptability Operating temperature -40℃ to 65℃ (environmental chamber test, temperature gradient 2℃ / min), IP55 protection (IEC 60529 standard, waterproof and dustproof rating 5), vibration resistance (40Hz, 6g, MIL-STD-810G, 2 hours for each of the three axes), salt spray test (5% NaCl, 120 hours, ASTM B117, no corrosion spots), electromagnetic compatibility (EN 61000-6-2, electric field strength 10V / m). The fuel cell stack shell uses a ceramic coating (ZrO2 based, thickness 0.4±0.05mm, thermal conductivity 0.5±0.1W / m·K, cost 350±10CNY / m). 2 ), surface temperature <40℃.
[0095] (6) Detection and verification methods The fuel cell stack was tested using ultrasonic non-destructive testing (frequency 6.5±0.5MHz, defect resolution 0.08mm, probe diameter 5mm); airtightness was determined using the helium differential pressure method (0.25±0.05MPa, leak rate <0.0018sccm / cm). 2 The detection time was 30 seconds. Performance was monitored via online data acquisition (2.5Hz, accuracy ±0.05%, data storage 1TB), with anomaly alarms (temperature >850℃, leakage >0.01sccm / cm, response time <0.2 seconds). The electrolyte's mechanical properties were verified by nanoindentation (Hysitron TI 950, load 10mN, hardness 8±0.5GPa); the electrode's catalytic activity was confirmed by cyclic voltammetry (scan rate 5mV / s, potential window 0-1V).
[0096] In summary, the technical solution of this application has at least the following advantages: (1) The two-stage electrolyte structure enables the stack to achieve high power density in the range of 600℃~800℃, reaching 0.84±0.02W / cm² at 600℃. 2 At 650℃, the W / cm² temperature reaches 0.98±0.02 W / cm². 2 At 800℃, the W / cm² reaches 1.27±0.03 W / cm². 2 The open-circuit voltage is 1.07±0.01V, and the internal resistance is 0.16±0.02Ω·cm. 2 Compared to the traditional YSZ fuel cell stack (600℃: 0.48W / cm³), 2 Internal resistance 0.3Ω·cm 2 Performance was improved by 75±5%. Conductivity optimization of YSZ and SDC ( Figure 4 This ensures that the fuel cell stack remains highly efficient in the mid-temperature range, making it suitable for distributed generation and portable power supplies. Figure 3 The IV curves visually demonstrate the increase in power density at different temperatures, proving the advantages of the fuel cell stack's mid-temperature performance.
[0097] (2) The fuel cell stack was tested at 650℃ for 20,000 hours (0.5A / cm). 2 The attenuation rate is only 4.5±0.2%, significantly better than that of traditional SOFC (12±3%). The low porosity of SDC (2.5±0.2%) and the optimized YSZ-SDC interface (resistance <0.007Ω·cm) further enhance its advantages. 2 The synergistic effect of these technologies reduced electrolyte degradation, while the Ni-YSZ anode (agglomeration rate <4%) and LSM-YSZ cathode (Sr segregation <1.8%) ensured electrode stability. X-ray diffraction (XRD) and transmission electron microscopy (TEM) analyses confirmed the absence of phase transition in the electrolyte and electrode grain growth <8%. Figure 6 The decay rate curve (0-20000 hours) demonstrates the ultra-long lifespan of the fuel cell stack, highlighting its structural stability and material durability.
[0098] (3) The fuel cell stack passed 200 thermal cycles (500℃~800℃, heating rate 10℃ / min) and the power density decayed by only 2.2±0.3%, thanks to the interface gradient layer (bonding strength 68±4MPa) and thermal stress optimization (82±3MPa). Figure 5 Rapid start-up from room temperature to 600℃ takes only 13.5 ± 0.5 minutes (heating power 2.8 kW), with a load change of 0.3 A / cm. 2 ~0.7A / cm 2 The response time is 1.6 ± 0.1 seconds, which is better than the traditional SOFC (startup > 20 minutes, response > 3 seconds). Figure 7 The response time curves validate rapid start-up and load adaptability, making it suitable for dynamic operating conditions such as traffic power systems.
[0099] (4) The stack supports H2 / CH4 mixed fuel (CH4 content ≤50%), with a reforming efficiency of 95±1% (steam / carbon ratio 1.8), and is resistant to H2S (150ppm, 3000 hours, decay <3%) and CO (200 periodontitis, 2000 hours, no poisoning). Figure 6 The fuel adaptability data demonstrates tolerance to CH4 and H2S. The stack operates in environments ranging from -30°C to 55°C, is IP55 protected, vibration resistant (30Hz, 4g), and has passed salt spray testing (5% NaCl, 72 hours) and EMC testing (EN 61000-6-2), ensuring reliability in harsh environments. Figure 5 The thermal stress distribution verifies the structural adaptability.
[0100] (5) Through large-scale production (3000kW per year) and the reduction of domestic material costs: material cost optimization (YSZ: 300 yuan / kg, SDC: 315 yuan / kg), equipment depreciation is reduced to 560 yuan / kW for an annual production of 3000kW, and the total cost is 3220±105 yuan / kW, which is close to the commercialization target (2100 yuan / kW~2800 yuan / kW). Automated casting (thickness deviation ±1.5μm), spraying (deposition deviation <1.5%) and modular design (replacement time <30 minutes) reduce production and maintenance costs.
[0101] (6) The stack thermal efficiency is 67±2% (fuel utilization rate 78±2%, air utilization rate 32±2%), which is better than that of traditional SOFC (approximately 55%). Safety is ensured by over-temperature protection (trigger 860℃, response <0.3 seconds), gas leakage alarm (sensitivity 0.005sccm / cm, response <0.4 seconds) and heat insulation coating (surface temperature <42℃). Figure 2 The temperature distribution curves demonstrate the uniformity and safety of thermal management. Figure 7 The rapid startup data further verifies the system's reliability.
[0102] While specific embodiments of this application have been described in detail, this should not be construed as limiting the scope of protection of this application. Various modifications and variations that can be made by those skilled in the art without inventive effort within the scope described in the claims still fall within the scope of protection of this application.
Claims
1. A SOFC stack containing a two-stage electrolyte, characterized in that, This includes high-temperature electrolytes, transition layers, and medium-temperature electrolytes bonded through co-sintering; among which... The high-temperature electrolyte is made of 8 mol% yttrium-stabilized zirconium oxide film with a thickness of 98 μm to 102 μm; the medium-temperature electrolyte is made of 20 mol% samarium-doped cerium oxide film with a thickness of 48 μm to 52 μm; the transition layer is made of a composite material of yttrium-stabilized zirconium oxide and samarium-doped cerium oxide with a thickness of 4.5 μm to 5.5 μm; the temperature ranges of the high-temperature electrolyte and the medium-temperature electrolyte are 797℃ to 713℃ and 587℃ to 603℃, respectively.
2. The SOFC stack containing a two-stage electrolyte according to claim 1, characterized in that, The yttrium-stabilized zirconia film is prepared by the following method: yttrium-stabilized zirconia powder, binder, plasticizer, and mixed solvent are weighed according to a mass ratio of (62~65):(3~4):(2~3):(30~31), stirred evenly, and then sintered; wherein the sintering temperature is 1380℃~1420℃, the holding time is 4h~6h, the heating rate is 4℃ / min~5.0℃ / min, the cooling rate is 2℃ / min~3℃ / min, and the sintering atmosphere is pure oxygen atmosphere.
3. The SOFC stack containing a two-stage electrolyte according to claim 1, characterized in that, The samarium-doped cerium oxide film was prepared by the following method: samarium-doped cerium oxide, dispersant, thickener and deionized water were weighed according to the mass ratio of (58~60):(2~2.5):(0.3~0.4):(36~40), mixed evenly and then prepared by spray treatment and sintering treatment; wherein, the pressure of the spray treatment was 0.65MPa~0.7MPa, the temperature of the sintering treatment was 1280℃~1320℃, the holding time was 3h~4h, the heating rate was 3℃ / min~4℃ / min, and the cooling rate was 1.0℃ / min~2.0℃ / min.
4. The SOFC stack containing a two-stage electrolyte according to claim 1, characterized in that, The transition layer is prepared by 5 to 6 plasma spraying processes. The parameters of the plasma spraying process include: argon flow rate of 42 L / min to 44 L / min, hydrogen flow rate of 6 L / min to 7 L / min, power of 33 kW to 40 kW, spraying distance of 7 cm to 8 cm, and single spraying time of 7 s to 8 s. In the plasma spraying slurry, the concentration of yttrium-stabilized zirconium oxide decreases sequentially, while the concentration of samarium-doped cerium oxide increases sequentially.
5. The SOFC stack containing a two-stage electrolyte according to claim 1, characterized in that, The co-sintering treatment has a sintering temperature of 1340℃~1350℃, a holding time of 2.5h~3.5h, a heating rate of 3.0℃ / min~4.0℃ / min, and a cooling rate of 1.0℃ / min~1.5℃ / min. The atmosphere for the co-sintering treatment is a mixture of argon and hydrogen, with the hydrogen having a volume fraction of 7% to 8% and the flow rate of the mixture being 0.7 L / min to 0.8 L / min.
6. The SOFC stack containing a two-stage electrolyte according to claim 1, characterized in that, The SOFC stack forms a temperature gradient through an alumina-based heat exchanger, which is provided with corrugated microchannels with a length of 0.25 mm to 0.3 mm and a wave height of 0.25 mm to 0.3 mm. The fuel flow rate of the alumina-based heat exchanger is 0.55 L / min to 0.65 L / min, and the air flow rate is 2.0 L / min to 3.0 L / min.
7. The SOFC stack containing a two-stage electrolyte according to claim 1, characterized in that, The SOFC stack comprises repeatedly stacked individual cells, which, from bottom to top, include interconnects, sealing layers, anodes, high-temperature electrolytes, transition layers, medium-temperature electrolytes, cathodes, sealing layers, and connectors.
8. The SOFC stack containing a two-stage electrolyte according to claim 7, characterized in that, The anode is made of nickel-doped yttrium-stabilized zirconium oxide composite material with a thickness of 490 μm to 510 μm. The mass ratio of nickel oxide to yttrium-stabilized zirconium oxide in the nickel-doped yttrium-stabilized zirconium oxide composite material is (55~65):(35~45).
9. The SOFC stack containing a two-stage electrolyte according to claim 7, characterized in that, The cathode is made of La. 0.8 Sr 0.2 A composite material of MnO3 and yttrium-stabilized zirconium oxide with a thickness of 40 μm to 60 μm.
10. The SOFC stack containing a two-stage electrolyte according to claim 7, characterized in that, The sealing layer is made of BaO-CaO-Al2O3-SiO2 glass ceramic; the interconnect is made of 316L stainless steel with a LaCrO3 coating.